Dataset for the proteomic and transcriptomic analyses of perivitelline fluid proteins in Pomacea snail eggs - Mu, Huawei (2017)
This article describes how the proteomic and transcriptomic data were produced during a study of the reproductive proteins of Pomacea maculata, an aquatic apple snail laying colorful aerial eggs, and provides public access to the data. The data are related to a research article titled ‘An integrated proteomic and transcriptomic analysis of perivitelline fluid proteins in a freshwater gastropod laying aerial eggs’ (Mu et al., 2017) [1]. RNA was extracted from the albumen gland and other tissues and sequenced on an Illumina Hiseq. 2000. The assembled transcriptome was translated into protein sequences and then used for protein identification. Proteins from the perivitelline fluid of P. maculata were separated in SDS-PAGE and analyzed by LTQ-Orbitrap Elite coupled to an Easy-nLC. The translated transcriptome data are provided in this article. Proteomic data (.raw file format) are available via ProteomeXchange with the identifier PXD006718.